(untitled) (XXI Century. Spanish Literature and Culture, 2012)
Vicente Luis Mora analyses the importance of the visual image on the literature of today. He divides his essay in two parts-construction and reconstruction- suggesting that the visual image can be manipulated in order to distort reality itself. Reality can thus become a “make-believe”, a pretense to the eyes of the reader, as is illustrated in the excerpt from the novel of Rosa Maria Rodriguez Magda. This distortion of reality is best expressed today by television which offers us a distorted image of the world but presents it in such way as to make us believe it is the only true one. This issue is perfectly illustrated by the excerpts from Carrión´s Los Muertos, J.F. Ferre´s Providence, and Vila´s Aire Nuestro.